FORMULASI DAN UJI AKTIVITAS SEDIAAN GEL ANTIACNE EKSTRAK ETANOL DAGING KURMA (Pheonix dactylifera L.) TERHADAP BAKTERI Propionibacterium acnes & Pseudomonas aeruginosa - Marbun, Nova rianti; Br Sembiring, Tio Ranti Sari (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
Acne (acne vulgaris) is a skin inflammation caused by the overgrowth of bacteria such as Propionibacterium acnes and Pseudomonas aeruginosa. This study aims to formulate a gel preparation containing ethanol extract of date flesh and evaluate its antibacterial activity. The extract was obtained via maceration using 70% ethanol. The gel was formulated in three extract concentrations: 10%, 20%, and 30%. Physical evaluations of the gel included organoleptic properties, homogeneity, pH, spreadability, and adhesiveness, while antibacterial activity was tested using the disk diffusion method. The results showed that the 30% concentration provided the largest inhibition zone against both test bacteria. Physical evaluations confirmed that the gel preparation met the criteria for a stable topical product. It can be concluded that the ethanol extract of date flesh can be effectively formulated into an antibacterial gel preparation and has potential as a natural antiacne product.